Integrated process for catalytic upgrading of hydrothermal liquefaction aqueous phase in the supercritical state - Kenney, David H.; Mosley, Alex; Suwannapong, Oamfah; Yazon, Jia; Kelkar, C. P.; Schmidt, Andrew J.; Tompsett, Geoffrey A.; Maag, Alex R.; Teixeira, Andrew R.; Timko, Michael T. (Frontiers in Chemical Engineering, 2025)
Hydrothermal liquefaction (HTL) is a waste agnostic process that leverages near-critical water to break down macromolecules, forming an energy-dense biocrude. Some carbon contained in the waste feed is lost in the aqueous phase, where its high organic content and unusual speciation are burdensome for municipal wastewater resource recovery facilities (WRRF). Treating the aqueous phase adds undesirable cost to the HTL process, reducing its attractiveness. Here, we report aqueous phase supercritical upgrading (AP-SCU) as a new catalytic aqueous phase upgrading technology that reduces the organic content of the aqueous phase with co-production of supplemental biocrude. The supercritical phase provides sufficient catalyst activity for organic conversion, reduces energy inefficiency by eliminating the need for evaporation, and extends the catalyst lifetime relative to the liquid state. AP-SCU was evaluated at 380–440°C at 24 MPa for a representative HTL aqueous phase produced from the treatment of food waste. Using a ZSM-5 catalyst bound with silica sol, the aqueous carbon content was reduced by 64%–73% with a corresponding production of aromatic hydrocarbons including phenol and 2-pentanone. The total nitrogen was reduced by approximately 10%. Additionally, the ZSM-5 facilitated reduction and denitrogenation reactions of aqueous phase compounds to produce aromatic and pyridine compounds which more closely resemble HTL biocrude. After 3 h on stream, the catalyst experienced coke formation, and surface degradation which led to a reduction in acid sites and surface area. The carbon balance for the system was closed through the analysis of the aqueous, solid, and gas phases to estimate that biocrude yield varies from 43%–57% on a carbon basis. An energy balance for HTL process with integrated AP-SCU system showed that operating the AP-SCU unit at 380°C yielded the minimum energy demand for carbon removal at 63 MJ/kg-TOC. This value is greater than the energy demand for conventional WRRFs (37.9 MJ/kg-TOC) but is more than 10-times less than emerging technologies which are designed to handle complex feeds. AP-SCU has potential as an energy efficient and effective new technology for reducing the TOC of the aqueous phase with simultaneous production of supplemental biocrude to offset energy demand.